IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN AKIDAH AKHLAK DI MTS MUHAMMADIYAH ALAMANDA KINALI PASAMAN BARAT - Elfia Rosa; Januar; Hamdi; Alimir (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract. This research is that the learning process is still centered on the teacher which makes the teaching and learning process passive and also the teacher only uses conventional models. This will have an impact on students' enthusiasm for learning to be low. "Students' success in learning cannot be separated from the teacher's success in determining the right learning model for their students. Learning models play an important role in more effective activities in teaching and learning, therefore determining the right learning model will produce quality learning. This research aims to find out how moral belief teachers implement the Problem Based Learning model in class VIII MTs. This type of research is descriptive qualitative. Data collection techniques using observation, interviews and documentation." Key Information for Teachers of Aqidah Akhlak. Supporting information is class VIII-A students and the school principal. The results of this research show that students' interest in learning about Aqidah Akhlak using a problem-based learning model is in the very good category, because students can explore further about problems that are closely related to everyday life and are also able to think critically and mutually work together in groups to solve the problems presented in the lesson.